PERAN BLOCKCHAIN DALAM MEWUJUDKAN EFISIENSI DAN KEAMANAN TRANSAKSI BISNIS - Agnes Tasya Goh; Dirza Satrio; Frans Poda Sihombing; Maderta Siburian; Michael Randu Gusti Silalahi; Joosten (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the role of blockchain technology in enhancing the efficiency and security of business transactions. Blockchain, as a decentralized, transparent, and immutable digital ledger system, provides solutions to various weaknesses of conventional systems, such as high transaction costs, operational inefficiencies, and risks of data manipulation. The research method employed is a literature review that examines scientific publications, articles, and reports on blockchain implementation in business sectors, particularly banking and accounting. The findings indicate that blockchain adoption can reduce transaction costs and processing time, improve transparency, and strengthen data integrity through consensus mechanisms and smart contracts. Moreover, blockchain has the potential to create new, accountable, and trustworthy business ecosystems. However, challenges related to regulation, technological adoption, and vulnerabilities to certain types of attacks remain to be addressed. Overall, blockchain significantly contributes to achieving efficiency and security in business transactions in the digital era.